Mystics in Novel Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha (Study of Sociology of Literature) - Deftita Yusantia; Aruna Laila; Wahyudi Rahmat (ppjbsip, 2019)
Mystic is one part that is portrayed and narrated by characters related to the occult or things that do not make sense. One of them is mysticism which is told in the novel Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha. Mystical events that begin with red shoes for your character that make each trip produce a mysterious story and always related to another trip. The purpose of this study was to describe the mystical element in the novel Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha. This type of research is qualitative research with the research method is descriptive analysis. The stages of this research are carried out by: (1) reading and understanding the novel Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha as a whole; (2) the incomparable adventure found in the Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu; (3) classifying data according to the inventory data format; and (4) entering data in the format of data inventory. After conducting research on the novel Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha obtained the following results: (1) not mystical which produces things that are collected (2) not mystical resulting in causes that are not ratios (3) not mystical. Third, it is not a mystical event or an extraordinary thing that cannot be accepted by human common sense contained in the novel Gentayangan Gentayangan Pilih Sendiri Petualangan Sepatu Merahmu by Intan Paramaditha.